Empagliflozin Ammeliorates High Glucose Induced-Cardiac Dysfuntion in Human iPSC-Derived Cardiomyocytes - Kwong-Man Ng (Nature Portfolio, 2018)
Abstract Empagliflozin, a sodium-glucose co-transporter (SGLT) inhibitor, reduces heart failure and sudden cardiac death but the underlying mechanisms remain elusive. In cardiomyocytes, SGLT1 and SGLT2 expression is upregulated in diabetes mellitus, heart failure, and myocardial infarction. We hypothesise that empagliflozin exerts direct effects on cardiomyocytes that attenuate diabetic cardiomyopathy. To test this hypothesis, cardiomyocytes derived from human induced pluripotent stem cells (hiPSCs) were used to test the potential effects of empagliflozin on neutralization of cardiac dysfunction induced by diabetic-like cultures. Our results indicated that insulin-free high glucose culture significantly increased the size of and NPPB, SGLT1 and SGLT2 expression of hiPSC-derived cardiomyocytes. In addition, high glucose-treated hiPSC-derived cardiomyocytes exhibited reduced contractility regardless of the increased calcium transient capacity. Interestingly, application of empagliflozin before or after high glucose treatment effectively reduced the high glucose-induced cardiac abnormalities. Since application of empagliflozin did not significantly alter viability or glycolytic capacity of the hiPSC-derived cardiomyocytes, it is plausible that empagliflozin exerts its effects via the down-regulation of SGLT1, SGLT2 and GLUT1 expression. These observations provide supportive evidence that may help explain its unexpected benefit observed in the EMPA-REG trial.